The Dilemma of Hemispherectomy for Rasmussen's Encephalitis in a Neurologically Intact Child - Borlot, Felippe; Yau, Ivanna; Olivieri, Heather; Ibrahim, George M.; Snead III, O. Carter (Journal of Pediatric Epilepsy, 2020)
Rasmussen's encephalitis is a rare drug-resistant focal epilepsy characterized by progressive hemiparesis, hemianopia, and cognitive decline. Hemispherectomy is currently the only known treatment that can be curative, though expected to cause postoperative motor and visual deficits in children and adolescents. To date, medical treatment with antiseizure medications and immunosuppressive agents can only offer partial, delayed, or temporary alleviation of symptoms. Hence, patients and families are often faced with the difficult decision to consider the possibility of seizure freedom at the cost of incurring permanent deficits. Here, we discussed the unique ethical issues when faced with a cure that can cause harm, and also discussed a shared decision-making approach guided by informed consent, principles of autonomy, and patient-centered values.
Keywords: Rasmussen's encephalitis; hemispherectomy; ethics; autonomy; shared decision-making